2011
DOI: 10.3382/ps.2010-01069
|View full text |Cite
|
Sign up to set email alerts
|

Production performance and nitrogen flow of Shaver White layers housed in enriched or conventional cage systems

Abstract: Despite the large number of studies examining the impact of cage systems on Ca and P nutrition, data are limited on the N balance of hens when housed under different systems. To this end, an experiment was conducted to assess N balance, manure characteristics, and indices of the performance of laying hens housed in 2 distinct caging systems. A total of 4,836 commercial Shaver White hens were housed in either enriched (EC) or conventional (CC) cages (average floor space per bird of 643 and 468 cm(2), respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
2
8
2
Order By: Relevance
“…However, AMC concentrations for PMAs 4 to 6 were between 0.56 and 0.58 ppm greater than those for PMA 7 and 8. These results do not agree with those reported by Neijat et al [ 62 ], which state that when manure is compacted (as in piles) the moisture content is greater than when it is dispersed in a thin layer, with more surface contact with the air, which promotes drying and therefore reduces NH 3 volatilization. It is important to take into account that usage of wood shavings or other material to counter humidity was low during PMA 2.…”
Section: Resultscontrasting
confidence: 85%
“…However, AMC concentrations for PMAs 4 to 6 were between 0.56 and 0.58 ppm greater than those for PMA 7 and 8. These results do not agree with those reported by Neijat et al [ 62 ], which state that when manure is compacted (as in piles) the moisture content is greater than when it is dispersed in a thin layer, with more surface contact with the air, which promotes drying and therefore reduces NH 3 volatilization. It is important to take into account that usage of wood shavings or other material to counter humidity was low during PMA 2.…”
Section: Resultscontrasting
confidence: 85%
“…Details on the experimental design for this study have been previously reported (Neijat et al, 2011). In brief, Shaver White pullets, obtained from Manitoba Perfect Pullets Ltd. (Rosenort, MB, Canada), were stocked at a commercial level (4,836 hens) from the age of 19 wk in cages under semicontrolled environmental conditions and were provided with 15 h of light/day.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, overall mean manure Ca excretion was found to be significantly lower in the EC than CC birds (2.11 vs. 2.29 ± 0.04 g/hen per day, respectively; P < 0.01). This was based on analyzed manure output for EC and CC hens (34.1 vs. 31.0 ± 0.32% DM output, respectively; P < 0.0001; Neijat et al, 2011).…”
Section: Calcium Balance/retention and Excretion In Manurementioning
confidence: 99%
See 1 more Smart Citation
“…For laying hens, nitrogen balance flows determined recently (2011) in hens smaller than French laying hens provided the following orders of magnitude: for a mean ingestion of 3 g of nitrogen/day, 20% are retained by the animal, 33% are exported into eggs and 65% are excreted in droppings. A well-balanced diet significantly increases the retention rate of ingested proteins as several studies have shown a reduction of nitrogen excretion of up to 40% (Neijat et al, 2011).…”
Section: Poultrymentioning
confidence: 99%